2021
DOI: 10.2147/cpaa.s278978
|View full text |Cite
|
Sign up to set email alerts
|

Successful Control of Hypoglycemia with Pasireotide LAR in a Patient with Inappropriate Insulin Secretion

Abstract: Introduction Inappropriate insulin secretion could be due to several diseases. Nesidioblastosis is characterized by diffuse hyperplasia of pancreatic beta cells, causing organic hypoglycemia. No pancreatic lesions are found on the imaging of patients with this condition. Diazoxide is used as a first-line treatment but can be poorly tolerated because of its side effects, and therapeutic failure is possible. Somatostatin analogues have limited efficacy because of their poor affinity to somatostatin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Kato et al [ 17 ] reported a case of adult-onset nesidioblastosis which was successfully treated with pancreaticoduodenectomy and octreotide, but their poor affinity to somatostatin receptors resulting in reduced efficiency. Pasireotide is another somatostatin analogue with a higher affinity to somatostatin receptors, and its long-acting release has been proved effective in isolated nesidioblastosis[ 18 ]. Other medications include glucocorticoids and calcium channel-blocking agents.…”
Section: Discussionmentioning
confidence: 99%
“…Kato et al [ 17 ] reported a case of adult-onset nesidioblastosis which was successfully treated with pancreaticoduodenectomy and octreotide, but their poor affinity to somatostatin receptors resulting in reduced efficiency. Pasireotide is another somatostatin analogue with a higher affinity to somatostatin receptors, and its long-acting release has been proved effective in isolated nesidioblastosis[ 18 ]. Other medications include glucocorticoids and calcium channel-blocking agents.…”
Section: Discussionmentioning
confidence: 99%
“…Rina Kato et al reported a case of adult-onset nesidioblastosis which was successfully treated with pancreaticoduodenectomy and octreotide [17] , but their poor affinity to somatostatin receptors resulting in reduced efficiency. Pasireotide is another somatostatin analogue with a higher affinity to somatostatin receptors, and its long-acting release has been proved effective in isolated nesidioblastosis [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer, colorectal cancer, pancreatic cancer, bladder cancer, and breast cancer have been reported to have a limited expression of SSTR1-4 and an increased expression of SSTR5, which may suggest potential benefits from the use of PAS in these diseases. [7,[98][99][100]. A study on the use of PAS in malignant melanoma (NCT01652547) has been recently completed; however, its results have not yet been published.…”
Section: Neoplasmsmentioning
confidence: 99%